Ethanol Policy Effects on US Natural Gas Prices and Quantities - Whistance, Jarrett; Thompson, Wyatt W; Meyer, Seth D (American Economic Review, 2010)
Ethanol Policy Effects on U.S. Natural Gas Prices and Quantities by Jarrett Whistance, Wyatt W. Thompson and Seth D. Meyer. Published in volume 100, issue 2, pages 178-82 of American Economic Review, May 2010